PENGARUH STRUKTUR CORPORATE GOVERNANCE DAN UKURAN PERUSAHAAN TERHADAP MANAJEMEN LABA (Studi Empiris pada Perusahaan Jasa Non Keuangan yang terdaftar di Bursa Efek Indonesia 2009-2011) - Arlita Marcela Sudibyo; Arifin Sabeni (Diponegoro Journal of Accounting, 2013)
This research aims to examine the influence of, corporate governance, and size towards earnings management in non financial services companies. Corporate governance in this research intersect in three variables, such as managerial ownership, institutional ownership and the proportion of independent board commisioner. The firm size measured by using the natural logaritma of total assets.This research was conducted by using documentary method from ICMD and annual reports of companies. The analysis method of this research using multiple regression. This study using data from non financial services companies  liked in Bursa Efek Indonesia (BEI) in 2009 until 2011. Sample of this study are 60 non financial services companies. Based on the result of the research, it shows that variable which has a significance influences is the managerial ownership, and institutional ownership. The increasingly managerial ownership, and institutional ownership, can make earnings management decrease in that non financial services companies. The proportion of independent board commisioner variable and firm size variable does not have a significance influence on the earnings management at non-financial services companies.